Evaluation of Tryptophan/Kynurenine Pathway Relevance With Immune System Biomarkers of Low Energy Trauma Hip Fractures in Osteoporotic Patients - Ercan DİNÇEL,; Yeşim ÖZKAN,; Murat ŞÜKÜROĞLU,; Hakan ÖZSOY,; Aylin SEPİCİ DİNÇEL, (Archives of Rheumatology, 2017)
Objectives: This study aims to evaluate tryptophan degradation and clarify whether altered levels of kynurenine and tryptophan (Kyn/Trp) ratio could be correlated to osteoporotic hip fractures via immune system. Patients and methods: The study included 60 patients with osteoporotic hip fracture (20 males, 40 females, mean age 76.6±6.9 years; range 59 to 95 years). Patients were divided into two as patients with collum femoris fractures (group 1; n=23) and intertrochanteric fractures (group 2; n=37). Fifteen healthy subjects without any fracture were selected as control group (group 3; 3 males, 12 females; mean age 69.7±8.4; range 60 to 86 years). All fractures were simple falls due to low energy trauma. Bone mineral density measurements were performed with Lunar dual energy X-ray absorptiometry. Kyn/Trp levels were measured by high performance liquid chromatography. Interleukin (IL)-6 and IL-1 beta levels were measured with solid-phase sandwich enzyme-linked immunosorbent assay. Results: All bone mineral density values were in agreement for osteoporosis and there was no significant difference between the two groups. Higher Kyn/Trp ratios were observed in groups 1 and 2 compared to group 3. This difference was more significant in group 1 (p=0.0001) than that in group 2 (p=0.048). Also, group 1 had significantly higher Kyn/Trp ratio than group 2 (p=0.011). There were significantly higher IL-6 and lower IL-1 beta levels both in groups 1 and 2 compared to group 3 (p=0.0001). There was no significant difference between group 1 and group 2 in terms of IL-6 and IL-1 beta levels. There was positive correlation with Kyn/Trp ratio (r=0.581, p=0.004) in group 2. Also, significant correlation was detected between IL-6 and IL-1 beta levels in the same group (r=0.665, p=0.036). Conclusion: Both increased degradation of tryptophan and ratio of Kyn/Trp indicate the relationship of immune activation with bone healing.